Faktor yang Mempengaruhi Organisasi Profesional: Studi Literature - Iqbal, Muhammad; Asrofiyah, Muflikhatul; Widodo, Agung; Kautsarin, Raisa; Ansori, M. Isa (Jurnal Ilmu Manajemen, 2024)
In this era of development, companies are competing to have employees who have capable performance, such as leadership attitudes, effective communication, work culture, work environment, performance, organizational effectiveness, work enthusiasm and work ethic. So that good performance in the organization will be created. This research is descriptive qualitative research. By using literature study research methods from scientific journals. The results of this research show that there are factors that influence individuals in organizing professionally. And from this research it can be concluded that the factors that influence professional organizations include leadership, effective communication, work culture, work environment, performance, organizational effectiveness, work enthusiasm and work ethic which aims to achieve goals in the organization.